2000
DOI: 10.2166/wst.2000.0405
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal from hydroponic culture wastewater by autotrophic denitrification using thiosulfate

Abstract: Using the upflow biological filter reactor, sulfur denitrification using thiosulfate of hydroponic culture wastewater was examined. Start-up periods of the reactor were one to two weeks. About 90% of nitrogen removal ratio were achieved over 80 days, at 6.3 kg/m3·days of nitrogen loading. Shock loading among 0.56-2.8 kgN/m3· day did not affect the reactor performance. However, when temperature went below 15°C, the effluent characteristics became poor. Suitable S/N and IC/N ratios were calculated as 3.3 and 0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Yamamoto-Ikemoto et al (2000) also observed that specific sulfur denitrification activities using thiosulfate were 2-5 times greater than that using elemental sulfur. However, elemental sulfur was mainly used for autotrophic denitrification because of its cost effectiveness, high sulfur content to mass ratio among the reduced sulfur compounds, and ease of handling (Hashimoto et al, 1987;Batchelor and Lawrence, 1978).…”
Section: Effects Of Different Sulfur Sources On Autotrophic Denitrifimentioning
confidence: 87%
“…Yamamoto-Ikemoto et al (2000) also observed that specific sulfur denitrification activities using thiosulfate were 2-5 times greater than that using elemental sulfur. However, elemental sulfur was mainly used for autotrophic denitrification because of its cost effectiveness, high sulfur content to mass ratio among the reduced sulfur compounds, and ease of handling (Hashimoto et al, 1987;Batchelor and Lawrence, 1978).…”
Section: Effects Of Different Sulfur Sources On Autotrophic Denitrifimentioning
confidence: 87%
“…Mixed sulphide and thiosulphate provide an opportunity to expedite nitrogen removal in the subsequent anoxic reactor. Not only does thiosulphate act as an electron donor for autotrophic denitrification (AD) as does sulphide [12,13], but it also induces faster AD than that on sulphide [14]. Compared with sulphate reduction, sulphite reduction demands less organics, thus making a small portion of organics remained possibly after biological sulphur reduction (BSR).…”
Section: Introductionmentioning
confidence: 99%
“…Advantages of autotrophic sulfur oxidizing denitrification for wastewater treatment include: (1) high nitrate removal efficiencies, (2) elemental sulfur, which is a by-product of oil processing, is less expensive than ethanol or methanol, (3) little or no external carbon source is required, minimizing the possibility of carry-over of excess organic carbon into the effluent, (4) sulfur oxidizing denitrification can take place under aerobic conditions (Yamamoto-Ikemoto et al, 2000). Although more biomass is produced, this eliminates the need to deoxygenate the influent wastewater, (5) due to lower biomass yields for autotrophic bacteria, less sludge is produced and (6) autotrophic sulfur oxidizing denitrifying bacteria produce less N 2 O (a greenhouse gas) than heterotrophic denitrifying bacteria (Park et al, 2002).…”
Section: Sulfur Oxidizing Denitrificationmentioning
confidence: 99%